2016 year in review: state advanced energy legislation - Hoffer, Katherine Heriot, author; Cook, Jeffrey J., author; Lyng, Jeff, author; Plant, Tom, author; Center for the New Energy Economy, publisher (Colorado State University. Libraries, 2016)
As of mid-December, 344 advanced energy-related bills have been enacted across the country. The Center for the New Energy Economy (CNEE) has identified three key highlights.
Keywords: Energy policy; Renewable energy sources -- Law and legislation -- United States